2019
DOI: 10.1039/c9ra08945d
|View full text |Cite
|
Sign up to set email alerts
|

PFOM fillers embedded PVDF/cellulose dual-layered membranes with hydrophobic–hydrophilic channels for desalination via direct contact membrane distillation process

Abstract: In this research work, novel perfluorooctanoic acid-modified melamine (PFOM) was synthesized as a hydrophobic filler using a facile one-pot synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The authors observed more finger-like macro-voids due to the non-solvent water transfer rate. Similarly, Arumugham et al [42] studied the performance of the PVDF membrane after adding perfluorooctanoic acid-modified melamine (PFOM) as a hydrophobic filler. The membrane preparation technique used was phase inversion, and results indicated improved mechanical strength and hydrophobicity.…”
Section: Phase Inversionmentioning
confidence: 99%
“…The authors observed more finger-like macro-voids due to the non-solvent water transfer rate. Similarly, Arumugham et al [42] studied the performance of the PVDF membrane after adding perfluorooctanoic acid-modified melamine (PFOM) as a hydrophobic filler. The membrane preparation technique used was phase inversion, and results indicated improved mechanical strength and hydrophobicity.…”
Section: Phase Inversionmentioning
confidence: 99%
“…The dynamic adhesion force between the liquid and the solid surface is used to quantify the droplet adhesion for evaluating the antiwetting property of that surface. , According to force balance, adhesion force ( F adhesion ) is equal to the projection of the drop’s gravity force ( F gravity ) in the direction of the motion (Figure B): To measure the interaction between water and surface, a high-sensitivity microelectromechanical balance system has been used. , The adhesion force between a droplet and surface correlates well with the variation in dynamic CAs (θ adv , θ rec , and θ SA ). , In addition, wetting force that is derived from eq is used to test the wetting capability While the attractive force (the tendency of the surface to either attract or repel water) on hydrophobic surfaces correlated well with θ adv , the adhesion force between surface and water correlated well with θ rec . , Gao et al proposed a laser deflection system based on a position-sensitive detector to measure the adhesion force of a drop of ionic liquid on a fluorinated silicon wafer in both static and kinetic regimes.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…23,80 In addition, wetting force that is derived from eq 4 is used to test the wetting capability. 85 F cos wetting sv sl lv…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[16][17][18][19] For application in MD, these membranes are often subjected to hydrophobization of their surfaces by nonpolar agents or components. 20 Commonly used nonpolar agents and components are perfluoroalkyl silanes, 21,22 perfluorocarbon polymers, 23 CNTs (carbon nanotubes), 24 CQDs (carbon quantum dots), 25 GOs (graphene oxides), 26 PS (polystyrene), 27 or alkylsilanes. [28][29][30][31][32] Among them, perfluoroalkyl silanes are widely studied and used in membrane surface hydrophobization because of their ease of implementation and high performance.…”
Section: Introductionmentioning
confidence: 99%